Inclusive Leadership and Diversity-Friendly Schooling: A Case Study from an Elementary School in Indonesia - Muhammad Bakhtiar Safari; Hermanto Hermanto (AL-ISHLAH: Jurnal Pendidikan, 2025)
Creating inclusive, diversity-friendly schools remains a major challenge in under-resourced educational settings. In Indonesia, particularly rural areas like East Lombok, limited infrastructure, absence of special education teachers, and rigid school culture hinder efforts toward educational equity. This study investigates how inclusive leadership practices can foster an inclusive school culture despite such systemic constraints. This research employed a qualitative single-site case study at Aikmel 02 Public Elementary School, purposively selected for its strong commitment to inclusive practices despite lacking formal inclusive school designation. Data were collected through in-depth interviews, direct observation, and document analysis, involving a principal and two experienced classroom teachers. Data were analyzed using the interactive model of Miles, Huberman, and Saldana (2014), with open thematic coding aligned with Carmeli et al.’s (2010) framework of inclusive leadership: openness, accessibility, and availability. Findings indicate that inclusive leadership was practiced through empathetic engagement with diversity, collaborative decision-making, flexible pedagogy, and strategic use of limited resources. The principal mobilized internal capacities, supported teacher autonomy, and facilitated external training partnerships. Despite systemic, cultural, and pedagogical barriers, adaptive strategies enabled meaningful inclusion for students with diverse needs. This study highlights how inclusive leadership in low-resource contexts can drive school-level transformation. By prioritizing trust, relational ethics, and collaborative culture, leaders can overcome structural limitations. The findings offer insights for policy development, school leadership training, and grassroots innovation in inclusive education.